Chum Salmon Genetic Diversity in the Northeastern Pacific Ocean Assessed with Single Nucleotide Polymorphisms (SNPs): Applications to Fishery Management. (2nd October 2015) - Small, Maureen P.; Rogers Olive, Serena D.; Seeb, Lisa W.; Seeb, James E.; Pascal, Carita E.; Warheit, Kenneth I.; Templin, William
Abstract: We examined genetic diversity patterns among 55 collections of Chum Salmon from the northeastern Pacific Ocean using 89 single nucleotide polymorphisms (SNPs). The distribution of Chum Salmon samples extended from the Nass River along the coast of British Columbia and along the coast of Washington as far south as the Columbia River. Chum Salmon represented three previously defined run‐groups: fall (primarily), summer, and winter. Genetic variation at SNP loci, as measured by F ST, ranged from 0.002 to 0.279 over all collections and averaged 0.062 over all loci. Similar to the genetic patterns detected with microsatellites and allozymes, genetic variation followed a regional structure along geographic distance, with genetic diversity being highest in the north and decreasing southward, then increasing in and near the Columbia River. Within Puget Sound, Washington, genetic variation was structured further according to run timing (fall, summer, and winter) and shared ancestry. Simulations indicated that this suite of SNPs is powerful for identifying regional components in a Chum Salmon mixed fishery. Because of the transferability of SNP data, the growing SNP baseline for Chum Salmon will be useful for multiple agencies managing Chum Salmon around the Pacific Rim. Received December 19, 2014; accepted May 20, 2015